Upper Extremity Peripheral Nerve Ultrasonography, as a Diagnostic Aid in Amyotrophic Lateral Sclerosis - Keivan Basiri; Hanieh Paydari; Fatemeh Abbasi; Behnaz Ansari (Advanced Biomedical Research)
Background: Amyotrophic lateral sclerosis (ALS) is a life-threatening progressive motor neuron disease whose diagnosis is challenging because of lacking specific diagnostic means. The current study aims to assess the value of upper extremity peripheral nerves ultrasonography in ALS detection. Materials and Methods: In this case-control study, 30 ALS subjects were assessed regarding the cross-sectional area (CSA) of the proximal (at distal part of arm or the proximal of elbow) and distal (at wrist level) median and ulnar nerves, assessed via ultrasonography. Similarly, 30 age- and gender-matched healthy controls were evaluated. The receiver operating curve (ROC) was depicted to determine a cut-point for ALS-associated peripheral nerve involvement. Results: Proximal CSA and the proximal-to-distal ratio of the median nerve was remarkably lower in both upper extremities of the ALS subjects compared to the controls (P value < 0.05), while the distal median nerve CSAs did not differ between the groups (P value > 0.05). Distal ulnar nerve CSA in the right hand (P value = 0.007) and the proximal ulnar nerve CSA in the left hand (P value = 0.001) were remarkably lower in the cases than the controls, but the other measurements did not differ (P value > 0.05). There was no significant cut-points to differentiate ALS-affected peripheral nerves from the healthy controls (P value > 0.05). Conclusion: Based on this study, CSA of the proximal median nerve in the cubital fossa seems a rational and valuable means to diagnose ALS; but the distal parts of the median nerve and the ulnar nerve in its all length remained a matter of debate.